Chemical, Sensory and Quality Evaluation of Cupcakes with Wheat Flour, Oat Flour and Strawberry Powder - Amira, M. A. Abd El-Salam; Esmat, S. Mohamed; Hanan, A. Hussien (Food Technology Research Journal, 2024)
Cupcakes are a popular treat enjoyed by people of all ages. This study aimed to develop cupcakes with improved nutritional value by incorporating whole-wheat oat flour and strawberry powder. Whole oat flour is a good source of protein, fat, and fiber compared to wheat flour. It also boasts the highest β-glucan content (1.69%), followed by wheat flour (0.13%). Additionally, oat flour is relatively high in magnesium, iron, and zinc. Strawberry powder, on the other hand, is a good source of calcium, iron, sodium, and potassium. Cakes made by substituting wheat flour with different levels of oat flour and 15% strawberry powder showed significantly higher levels of moisture, protein, ash, dietary fiber, beta-glucan, and carotene compared to the control group. Mineral content also increased significantly with the addition of 15% strawberry powder and different oat flour levels. However, incorporating both strawberry powder and whole oat flour into the cupcakes negatively impacted their volume and specific volume, while weight and density increased. Hardness and gumminess also increased with higher oat flour substitution. On a positive note, the addition of 15% strawberry powder led to an improvement in all sensory parameters measured. Up to 35% oat flour inclusion resulted in cupcakes with favorable odor, taste and texture.